Neuroscience for dummies - Amthor, Frank (--For dummies, 2016)
Neuroscience For Dummies gives the reader an understanding of the brain's structure and function, as well as a look into the relationship between memory, learning, emotions, and the brain. Providing insight into the biology of mental illness and a glimpse at future treatments and applications of neuroscience.